Synthesis of 3-Aryl-Substituted 4-Aminopyrazoles from Acetophenones - Stumpf, Andreas; Xu, Di; Tuck, Tyler A.; Zhang, Haiming (Synthesis, 2022)
A synthetic methodology for a protecting-group-free formation of 3-aryl-substituted 4-aminopyrazoles from acetophenones via a telescoped oximation and hydrazine condensation of 1,3-ketoaldehydes to generate nitrosopyrazoles, and copper-catalyzed NaBH4 reduction of the nitroso group, was demonstrated. The synthesis tolerates a broad scope of substrates with a variety of substituents on the phenyl ring to afford the desired products.
Keywords: 3-aryl-substituted 4-aminopyrazoles; oximation; 1,3-dielectrophile condensation; nitroso reduction; heterocycles